2018
DOI: 10.1073/pnas.1812704115
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of tumor microenvironment by nitric oxide impedes castration-resistant prostate cancer growth

Abstract: Immune targeted therapy of nitric oxide (NO) synthases are being considered as a potential frontline therapeutic to treat patients diagnosed with locally advanced and metastatic prostate cancer. However, the role of NO in castration-resistant prostate cancer (CRPC) is controversial because NO can increase in nitrosative stress while simultaneously possessing antiinflammatory properties. Accordingly, we tested the hypothesis that increased NO will lead to tumor suppression of CRPC through tumor microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…On the other hand, as a Mr. Hyde cytokine, IL-34 can be considered a good theraupeutic target against a wide range of diseases, from virus infections such as HCV or HBV, to autoimmune diseases such as RA, systemic sclerosis, systemic lupus erythematous, Sjogren's syndrome 139 and inflammatory bowel diseases, to cancer-like osteosarcoma, lung cancers, melanoma, colorectal cancer, ovarian tumors, prostate cancer 97 and hepatocellular carcinoma 100 , 101 . In the majority of these conditions, authors have reported that high levels of IL-34 in serum or tissue fluids correlated with poor prognosis and survival, and suggested using IL-34 as an indicator of disease grade 230 , 231 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as a Mr. Hyde cytokine, IL-34 can be considered a good theraupeutic target against a wide range of diseases, from virus infections such as HCV or HBV, to autoimmune diseases such as RA, systemic sclerosis, systemic lupus erythematous, Sjogren's syndrome 139 and inflammatory bowel diseases, to cancer-like osteosarcoma, lung cancers, melanoma, colorectal cancer, ovarian tumors, prostate cancer 97 and hepatocellular carcinoma 100 , 101 . In the majority of these conditions, authors have reported that high levels of IL-34 in serum or tissue fluids correlated with poor prognosis and survival, and suggested using IL-34 as an indicator of disease grade 230 , 231 .…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, tumor cells express IL-34, which induced TAM polarization into an M2 pro-tumorigenic phenotype with the properties of chemoresistance to tumor cells through Akt signaling pathway activation 96 . Another study showed that nitric oxide therapy reduced tumor progression and correlated with a decrease in the IL-34-derived TAM populations in tumorigenic castration-resistant prostate cancer xenografts 97 . Taken together, these observations suggest that IL-34 may play an essential role in both the pro-tumorigenic polarization of TAMs, and tumor progression, as revealed in various other cancers.…”
Section: From Monocytes To “Non-resident” Macrophagesmentioning
confidence: 99%
“…In CRPC, NO has been identified to play a role in the downregulation of AR, mediating the mechanism of resistance to this mainstay of treatment (Arora et al, 2018). The suggestion that NO downregulates transcription of the AR gene, causing an evolutionary selection pressure for aggressive CRPC, has been reproduced elsewhere (Cronauer et al, 2003).…”
Section: Prostate Cancer and No Therapeuticsmentioning
confidence: 99%
“…Additionally, the cytokines responsible for the differentiation of TAMs are also suppressed by NO. When xenografted mice were treated with NO, the tumor burden was suppressed for a number of weeks even though the half-life of NO is known to be seconds, indicating a potential longterm therapeutic effect (Arora et al, 2018). Another approach has been flavonoid administration from citrus peels, which have reduced tumor size, metastasis, and angiogenic growth in mouse models of human prostate cancer (Lai et al, 2013).…”
Section: Prostate Cancer and No Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation